1990
DOI: 10.1111/j.1360-0443.1990.tb00655.x
|View full text |Cite
|
Sign up to set email alerts
|

Is pregnancy a time of changing drinking and smoking patterns for fathers as well as mothers? An initial investigation

Abstract: This paper describes changing smoking and drinking patterns before and during pregnancy in 313 expectant couples. Fathers were more likely to drink and smoke more heavily than mothers throughout. Before pregnancy in only 42% of couples were both partners safe drinkers and non-smokers. This increased to 50% during pregnancy. Most mothers reduced alcohol consumption during pregnancy and although about half of the fathers also changed their drinking patterns, only about a fifth decreased their consumption. Levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
35
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 30 publications
(28 reference statements)
7
35
2
Order By: Relevance
“…In addition, pregnant women may be more likely to reduce their alcohol consumption if their partners also decrease their consumption (Waterson et al, 1990). Our study also demonstrated that the quality of the intimate partner relationship, specifi cally satisfaction with the relationship and ability to discuss problems with the partner, was lower among women who consumed moderate to heavy amounts of alcohol during pregnancy compared with light drinkers/abstainers, independent of other risk factors.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In addition, pregnant women may be more likely to reduce their alcohol consumption if their partners also decrease their consumption (Waterson et al, 1990). Our study also demonstrated that the quality of the intimate partner relationship, specifi cally satisfaction with the relationship and ability to discuss problems with the partner, was lower among women who consumed moderate to heavy amounts of alcohol during pregnancy compared with light drinkers/abstainers, independent of other risk factors.…”
Section: Discussionsupporting
confidence: 54%
“…An extensive body of literature, mostly from English-speaking countries, demonstrates that married or cohabiting partners tend to have similar substance use patterns, problem drinking, and alcohol use disorders . In expectant parents, a few prior studies reported positive associations between partners' levels of smoking and their levels of alcohol consumption (Everett et al, 2005(Everett et al, , 2007Waterson et al, 1990). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In two European observational studies, men and their pregnant partners were found to reduce smoking and drinking over the course of pregnancy (Hyssala, Rautava, Sillanpaa, & Tuominen, 1992;Waterson, Evans, & Murray-Lyon, 1990). A recent large-scale randomized controlled trial in Australia directed intervention to 561 expectant fathers during pregnancy and found that 16.5% in the experimental condition and 9.3% in the control condition quit smoking at 6 months postpartum (Stanton, Lowe, Moffatt, & Del Mar, 2004).…”
Section: Introductionmentioning
confidence: 96%
“…For example, research on breast-feeding has consistently identified fathers as an important source of support in the decision to breast-feed and its implementation (Bar-Yam and Darby, 1997;Wolfberg et al, 2004). Partners' smoking habits have been one of the strongest predictors of prenatal cigarette use (Olsen, 1993;Waterson et al, 1990). Maternal drinking is highly correlated with paternal drinking (Passaro et al, 1998), because the premarriage alcohol consumption of husbands has been found to be unilaterally influential on their wives' drinking after marriage (Leonard and Das Eiden, 1999;Leonard and Mudar, 2003).…”
Section: Abstract Objectivementioning
confidence: 99%